Identity, Justice and Resistance in the Neoliberal City - Erdi, Gülçin; Şentürk, Yıldırım (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book details the current neoliberal restructuring of cities and its impact on the rise and spread of resistance and uprisings in different cities throughout the world. Through close ethnographic study the authors illuminate the strategies adopted for everyday life that have evolved in response to the neoliberal managing of cities, by which the city is shaped by market forces rather than by the needs of its inhabitants. In the light of many urban movements, uprisings and forms of resistance observed in such diverse countries as Brazil, Turkey, the USA, Greece and Spain since the Arab uprising of 2011, this collection makes an original contribution to urban sociology and social geography by developing a spatial approach to understanding how the city shapes identities and perceptions of (in)justice. This innovative volume will be of interest to readers across the social sciences.
Keywords: Social sciences.; Ethnology.; Ethnography.; Sociology, Urban.; Human geography.; elektronické knihy; electronic books